2013
DOI: 10.1007/s10517-013-2010-y
|View full text |Cite
|
Sign up to set email alerts
|

Benzyloxycarbonyl-Methionyl-2(S)-Cyanopyrrolidine, a Prolyl Endopeptidase Inhibitor, Modulates Depression-Like Behavior of Rats in Forced Swimming Test and Activities of Proline-Specific Peptidases in the Brain Structures

Abstract: High activities of prolyl endopeptidase and dipeptidylpeptidase IV in the striatum and of prolyl endopeptidase in the frontal cortex were recorded in rats with stress-induced depression-like state (behavioral despair) developed in the Porsolt forced swimming test. Acute injection of benzyloxycarbonyl-methionyl-2(S)-cyanopyrrolidine (prolyl endopeptidase noncompetitive synthetic inhibitor) in a dose of 1 mg/kg prevented the development of behavioral despair and the increase of prolyl endopeptidase and dipeptidy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…DPP-IV-deficient rats demonstrated anxiolytic-like behavior and reduced stress-like responses [24]. In our studies, we have revealed increased activities of both DPP-IV and PEP in several brain structures in rat models of stress-induced depression-like state and experimental depressive-like syndrome associated with a dopamine deficit induced by the proneurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine [25] [26].…”
Section: Introductionmentioning
confidence: 53%
“…DPP-IV-deficient rats demonstrated anxiolytic-like behavior and reduced stress-like responses [24]. In our studies, we have revealed increased activities of both DPP-IV and PEP in several brain structures in rat models of stress-induced depression-like state and experimental depressive-like syndrome associated with a dopamine deficit induced by the proneurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine [25] [26].…”
Section: Introductionmentioning
confidence: 53%
“…In the models of stress-induced depression in rats in the forced swimming test and anxiety-depressive state induced by administration of DPP-IV inhibitor in the early postnatal period, the antidepressant effect of Z-Met-Prd-N was followed by normalization of PEP and DPP-IV activities in brain structures [1,9]. Analysis of changes in prolyl-specifi c endopeptidase activity and effi ciency of PEP inhibitors in various models of affective disorders during different administration regimens drove us to a conclusion that antidepressant activity is a common property of PEP inhibitors with various mechanisms, which opens prospects for creation of a group of antidepressants based on PEP inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments, the injections of methionyl-2(S)-cyanopyrrolidine, a synthetic DPP-IV inhibitor, to rats during the early postnatal period were found to induce the development of anxious-depressive syndrome in adolescent and adult rats [3]. It has been demonstrated on various models of affective disorders that activity of PEP and DPP-IV increases in rat brain structures involved in emotion and motivation behavior [1,2,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, POP located in activated microglia is a potential target for neuroprotection ( Natunen et al, 2019 ). Indeed, previous studies have shown that low molecular weight inhibitors of POP had pronounced neuroprotective, nootropic, antidepressant, and anxiolytic properties ( Penttinen et al, 2011 ; Krupina et al, 2013a ). Indeed, three POP inhibitors (JTP-4819, Z-321, and S 17092) are in phase I and/or II clinical trials, thus demonstrating that small molecule POP inhibitors could be safely administered in humans ( Svarcbahs et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%